Tricuspid regurgitation in His bundle pacing: A systematic review. Issue 6 (28th June 2022) - Zaidi, Syed Muhammad Jawad; Sohail, Hasan; Satti, Danish Iltaf; Sami, Abdul; Anwar, Mateen; Malik, Jahanzeb; Mustafa, Bilal; Mustafa, Mohammad; Mehmoodi, Amin
Abstract: Objective: This systematic review aimed to explore an association of new TR and its quantification in patients undergoing His bundle pacing (HBP). Methods: A literature review was conducted using Mesh terms (His bundle pacing, tricuspid regurgitation, tricuspid valve incompetence, etc.) in PubMed, EMBASE, Web of science CINAHL, and the Cochrane Library till October 2021. Relevant studies evaluating tricuspid regurgitation in HBP were included and information regarding TR and its related factors (ejection fraction (EF) and New York Heart Association (NYHA) class) were retrieved from the eligible studies. Results: Out of 196 articles, 10 studies met the inclusion criteria, which consisted of 546 patients with HBP. The mean age of the patients ranged between 61.2 ± 12.3 and 75.1 ± 7.9 years with 54.1% males. The overall implant success rate was 79.2%. Only one study reported a 5% incidence of TR, while 9 studies reported no new TR after HBP. Four studies reported overall decrease in TR by 1 grade and 3 studies demonstrated increased TR from baseline. Two studies showed no change from baseline TR. Conclusion: HBP causes improvement in TR grade after HBP for cardiac resynchronization therapy (CRT) as well as atrioventricular block (AVB). Further studies in the form of randomized controlled trials are required to further evaluate the effect of HBP on tricuspid valve functioning. Abstract : The overall implant success rate was 79.2%. Only one study reported a 5% incidence of TR while 9 studies reported no new TR after HBP. Four studies reported overall decrease in TR by 1 grade and 3 studies demonstrated increased TR from baseline. Two studies showed no change from baseline TR.